Sustitución de sistema de producción de vapor. - Vega-Solís, Esteban (Instituto Tecnológico de Costa Rica, 2002)
The company Products of Concrete S.A has made in this year a notorious change in the prefa process, what has caused modifications in the operation of other areas of the plant. One of those areas are the steam system. The vapor is used in the cured in the products like a way of accelerating the one forged and hardening of the pieces, maintaining to change a control on the final resistance. However, the cured tonnage in six months will be much smaller, approximately 65% less than that cured with the process of old prefabricated. The above-mentioned impels to the company to carry out a balance of the thermal load and to evaluate the components of the system (technological selection), aspects contemplated in this work. The second work consists on the implementation of a plan of preventive maintenance for the Planta Belén. The company has previous works on the topic, with the result that the work was undertaken of to standardize and to consolidate the existent inspections in an in agreement format with the current situation. This caused the necessity to revise the list of teams, to include teams that were not coded, to select them according to their criticism, to revise the technical material, to create an up-to-date format for the manual of inspections, to create the routes of inspections, to make the listing of critical teams and to define the sustainability of the plan, everything according to the way of operation of the plant.

La empresa Productos de Concreto S.A ha efectuado un cambio notorio en el proceso de prefabricado, lo que ha provocado alteraciones en el funcionamiento de otras áreas de la planta, incluyendo a la red de vapor. La cantidad de producto que requiere ser tratado por la caldera disminuirá aproximadamente un 65% dentro de seis meses debido a la entrada de nuevos procesos productivos. Lo anterior impulsa a la empresa a realizar un balance de la carga térmica y a evaluar cuáles de los componentes de la red de vapor deben ser cambiados para asegurar una alta eficiencia. Éste estudio recibe el nombre de selección tecnológica. El segundo trabajo consiste en la implementación de un plan de mantenimiento preventivo para la Planta Belén. La empresa tiene trabajos previos sobre el tema, de ahí que se emprendió la labor de uniformar y consolidar las inspecciones existentes en un formato acorde con la situación actual. Palabras claves: productos de concreto, red de vapor, curado con vapor, mantenimiento preventivo, equipo crítico.
Programa de mantenimiento preventivo
Proyecto de Graduación (Bachillerato en Ingeniería en Mantenimiento Industrial). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2002.
Keywords: Empresas; Organización; Equipo; Gas; Producción; Concreto